2018
DOI: 10.1007/s12602-018-9464-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved Viability of Microencapsulated Probiotics in a Freeze-Dried Banana Powder During Storage and Under Simulated Gastrointestinal Tract

Abstract: Freeze-dried banana powder represents an ideal source of nutrients and has not yet been used for probiotic incorporation. In this study, microencapsulation by freeze drying of probiotics Lactobacillus acidophilus and Lactobacillus casei was made using whey protein isolate (WPI), fructooligosaccharides (FOS), and their combination (WPI + FOS) at ratio (1:1). Higher encapsulation yield was found for (WPI + FOS) microspheres (98%). Further, microcapsules of (WPI + FOS) were used to produce a freeze-dried banana p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…The simulated gastric fluid (SGF) and simulated intestinal fluid (SIF) were performed as described by Massounga et al [ 37 ] with modifications. Briefly, for SGF, 3.5 g/L pepsin was suspended in 0.2% w/v sterile NaCl solution and adjusted pH to 2.0, made the total volume of the solution up to 100 mL, and filtered through a 0.22 μm filter membrane.…”
Section: Methodsmentioning
confidence: 99%
“…The simulated gastric fluid (SGF) and simulated intestinal fluid (SIF) were performed as described by Massounga et al [ 37 ] with modifications. Briefly, for SGF, 3.5 g/L pepsin was suspended in 0.2% w/v sterile NaCl solution and adjusted pH to 2.0, made the total volume of the solution up to 100 mL, and filtered through a 0.22 μm filter membrane.…”
Section: Methodsmentioning
confidence: 99%
“…The results for the microencapsulation yields of L. acidophilus microcapsules uncoated/coated with whey protein and/or xanthan are shown in Table 1. The microencapsulation yield is an important factor for assessing the effective encapsulation method and indicating the efficiency of the chosen encapsulating agents (Bora et al, 2019).…”
Section: Microencapsulation Yield and Physicochemical Properties Of Coated Lactobacillus Acidophilus Microcapsulementioning
confidence: 99%
“…It also facilitates the modification of physical, sensorial, and chemical attributes of the banana to meet consumer expectations, which ultimately increase the market value of the product. Drying of banana also felicitates a new horizon in different range of products (Jiang et al., 2013; Massounga Bora et al., 2019; Moraga et al., 2011). Many studies have been reported on the influence of process variables on the quality of dried banana (Da Silva et al., 2015; Nunes et al., 2013; Sousa and Marsaioli, 2016).…”
Section: Introductionmentioning
confidence: 99%